2015
DOI: 10.1002/2015jd023734
|View full text |Cite
|
Sign up to set email alerts
|

Lightning attachment processes of three natural lightning discharges

Abstract: Using a high-speed optical imaging system specifically designed for observing the lightning attachment process, we have documented the attachment process for six strokes in three natural lightning flashes. All strokes initiate at a height above ground and propagate bidirectionally from that height, similar to the return strokes of artificially initiated (triggered) lightning previously reported by Wang et al. (2013Wang et al. ( , 2014. Though the data are quite limited, these natural return strokes suggest a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…Wang et al . [, , ] and Carvalho et al . [, ] have described similar variations in the risetime and amplitude of the luminosity in the lowest 60 m of RS channels.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Wang et al . [, , ] and Carvalho et al . [, ] have described similar variations in the risetime and amplitude of the luminosity in the lowest 60 m of RS channels.…”
Section: Discussionmentioning
confidence: 57%
“…Olsen et al [2004] report events where the RS speed had a nonmonotonic behavior with height, i.e., it first increased and then decreased, and there was also significant attenuation and dispersion of the luminous front as the RS propagated upward. Wang et al [2013Wang et al [ , 2014Wang et al [ , 2015 and Carvalho et al [2015Carvalho et al [ , 2017 have described similar variations in the risetime and amplitude of the luminosity in the lowest 60 m of RS channels. Wang et al [2013Wang et al [ , 2016 have reported that the initiation heights of RS above the ground termination vary from about 7 to 21 m in RTL and appear to be correlated with the amplitude of the peak current in the RS that follows.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Note that this picture is quite different from that described by Wang et al . [] of a bifurcated channel, with terminations spaced by a few microseconds.…”
Section: Introducing the Rare Lightning Eventmentioning
confidence: 99%
“…We caution the reader that the velocities computed at the channel‐bottom may be affected by the unresolved bidirectional propagation of the return stroke wave. Our experimental setup was not designed to decompose these two waves propagating bidirectionally from their initiation height, but such decomposition has been done for both natural and triggered lightning [e.g., Wang et al ., , ]. We note that both cases with the time domain velocities greater than the speed of light were observed for the events triggered on or after 13 August 2014, when the photodiodes aimed at the channel‐bottom where separated by only 12 m, less than the lowest channel section separation of 28 m before 13 August 2014.…”
Section: Discussionmentioning
confidence: 81%